Rediscovery of Parahyparrhenia bellariensis (Poaceae: Andropogoneae): A presumed extinct grass from Andhra Pradesh, India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2021)
Parahyparrhenia bellariensis, an extremely rare and highly narrow endemic grass, has been rediscovered after almost 184 years from Cuddapah [Kadapa] district, Andhra Pradesh. The first description of its complete habit, basal portion and other features of the spikelets are provided along with new locality of its occurrence. In addition, photographs of the habitats, live plants, and a key to distinguish two Indian endemic species, distribution map and illustration are provided. As per the IUCN Red List Criteria this species is assessed here as Critically Endangered (CR). In order to facilitate the prospective conservation of this grass, we have discussed about the peculiarity of its habitat.